Firm innovation and co-location in Portugal - Faria, Ana Paula (2015)
This paper investigates the geographical distribution and concentration of firms’ innovation persistence and innovation type (product and process) based on three waves of the Portuguese Community Innovation Survey data covering the period 1998–2006. The main findings are: 1) both innovation persistence and innovation type are asymmetrically distributed across Portuguese regions, 2) the degree of correlation between geographical location and innovative output varies with the innovation type, and 3) the correlation between geographical unit and innovation increases when the spatial unit of analysis is narrower. The results suggest that the firms’ choices of geographical location have a long-lasting effect, engendering no equal probabilities of being persistently innovative.